Tax Avoidance Practices in Indonesia: The Impact of Transfer Pricing, Profitability, and Institutional Ownership in Mining Companies - Agustine Dwianika; Rafiq Ahmad (Proceedings International Conference on Sustainable Innovation (ICoSI), 2021)
Tax avoidance practices are efforts made by taxpayers so that tax payable can be minimized. Tax avoidance practices emphasize the efforts that can be done but does not violate the provisions or regulations of the appropriate tax laws. This study aims to examine the impact of Transfer Pricing, Profitability (ROA), Institutional Ownership on tax avoidance practices (tax avoidance). The population in this study were all companies in the mining sector listed on the Indonesia Stock Exchange (BEI) in 2015-2019 about 47 companies. The sample was determined using purposive sampling method, with a sample size of 32 samples consisting of 8 companies that have met the criteria for determining the sample. The data used in this study is secondary data obtained through the Indonesia Stock Exchange (BEI) website for the 2015-2019 period. The results of the research conducted show that Transfer Pricing has a significant effect on Tax Avoidance Practices, Profitability has a significant effect on Tax Avoidance Practices, and Institutional Ownership has a significant effect on Tax Avoidance Practices. Simultaneously they have a significant effect on Tax Avoidance Practices.